Two novel families with hemiplegic migraine caused by recurrent SCN1A mutation p.F1499L. (July 2018) - Schubert, Victoria; Auffenberg, Eva; Biskup, Saskia; Jurkat-Rott, Karin; Freilinger, Tobias
Background: Familial hemiplegic migraine type 3 is a monogenic subtype of migraine caused by missense mutations in the neuronal voltage-gated sodium channel gene SCN1A, with 10 different mutations reported so far. In two familial hemiplegic migraine type 3 families, partial cosegregation with a rare eye phenotype (elicited repetitive daily blindness) was previously reported. Methods: Two novel familial hemiplegic migraine pedigrees were subjected to genetic analysis and detailed work-up of associated clinical features. Results: In both pedigrees, we identified SCN1A mutation p.F1499L, which has been previously associated with familial hemiplegic migraine type 3 and elicited repetitive daily blindness. Both families displayed a pure familial hemiplegic migraine phenotype without evidence of an episodic eye phenotype. Conclusion: Like a substantial proportion of other familial hemiplegic migraine type 3 mutations, p.F1499L affects the intracellular linker between domains III and IV of SCN1A, which seems to be a mutational hot-spot. Our new data establish p.F1499L as a recurrent familial hemiplegic migraine type 3 mutation. Elicited repetitive daily blindness seems to be a rare phenomenon in familial hemiplegic migraine type 3, even in carriers of the same mutation.